HUBUNGAN KOPING RELIGIUS DENGAN TINGKAT DEPRESI PADA WARGA BINAAN WANITA DI LEMBAGA PEMASYARAKATAN - Akhmad Yanuar Fahmi; Ria Sukmawati (Jurnal Surya Muda, 2020)
Religious coping is a way to overcome depression experienced by a person by improving the individual's relationship with God. This study aims to determine the relationship between religious coping and depression level. This study uses a cross sectional with purposive sampling technique. a sample of 59 respondents using the DASS instrument. The results of the calculation of the Rank Spearmean statistical test obtained the Correlation Coefficient results of 0.447 and Sig. (2-tailed) = 0.000 <0.05 level (2-tailed), which means that Ho is rejected, there is a relationship between religious coping and the level of depression experienced by female inmates in Corrections. Female assisted residents who experience good religious coping, the prisoner does not experience depression or normalcy and vice versa.